Comparative Analysis of Gas Turbine Compressor Efficiency Before and After DuraVee-to-DuraGT Final Filter Replacement at PT. Energi Listrik Batam - Jhon Hericson Purba; Erik Manasse; Jihan Zeinyuta; Muhammad Veven (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Compressor performance is one of the primary factors influencing the thermal efficiency and power output of a gas turbine. The condition of the inlet air filtration system plays a crucial role in compressor performance, as it directly affects airflow resistance and inlet air conditions. This study aims to analyze and compare the compressor efficiency of Gas Turbine Unit 1 at PT Energi Listrik Batam before and after the replacement of the final filter from the DuraVee® XL98 type to the DuraGT™ V300F9 type. The operational data used in this study consist of historical unit data collected from several representative operating periods, including the period when the DuraVee® XL98 final filter was in service, the initial operating period of the DuraGT™ V300F9 filter, and the most recent operating condition after five years of using the new filter type. The analyzed parameters include compressor inlet air pressure and temperature, pressure ratio, gas turbine power output, and compressor efficiency. The analysis was conducted by comparing compressor efficiency values under each operating condition based on selected and processed actual plant operating data. The results indicate that replacing the final filter type from DuraVee® XL98 to DuraGT™ V300F9 improved gas turbine compressor efficiency by 0.53–1.10%, with an average increase of 0.75% across all load conditions.